Changes in the technological properties of sugar beet root crops during industrial storage in ventilated piles - Egorova Marina (EDP Sciences, 2021)
When storing sugar beets in natural conditions, transformations of the chemical composition occur in it, leading to the accumulation of non-sugars, which reduces the processing efficiency and sugar yield. The use of the technology of forced ventilation of the air environment of the kagats is aimed at reducing the negative impact of the ongoing processes. This study presents the results of changes in the technological properties of sugar beets during industrial storage of two types: in a ventilated rack, in a rack without ventilation. It was shown that forced ventilation of the air in the stagger led to slower development of diseases of root crops with stag rot, the processes proceeded 2 times slower. Changes in the chemical composition of sugar beets after 45 and 60 days of storage are shown. When sugar beets were stored in a ventilated stagger for 60 days, the daily decrease in sugar content was 1.6 times lower than when stored in a staggered rack without ventilation; the increase in the content of reducing substances is 3.5 times lower, α-amino nitrogen, potassium, sodium - on average 1.2 times lower. The calculated sugar yield for the storage conditions of sugar beets in a ventilated trough was 1.1 times higher than when stored in a trough without ventilation. It has been established that the creation of more favorable conditions for the air environment of the sugar beet pile through forced ventilation reduces the intensity of natural biochemical and microbiological processes in root crops, extends the shelf life of their technological properties, and ensures the economic efficiency of sugar production.